REPORT ON THE FIRST MOS-1 DATA RECEIVED AT SYOWA STATION, ANTARCTICA - ヤマノウチ, タカシ; カンザワ, ヒロシ; アリヨシ, ヒデトシ; エジリ, マサキ; YAMANOUCHI, Takashi; KANZAWA, Hiroshi; ARIYOSHI, Hidetoshi; EJIRI, Masaki (National Institute of Polar Research, 1991)
P(論文) Data from Marine Observation Satellite 1 (MOS-1) were received starting from February 1989 at Syowa Station, Antarctica, by the newly installed Multi Purpose Satellite Data Receiving System (11m antenna). The data of more than 200 paths are to be received per year, in order to study polar atmosphere, ice sheet and sea ice using three sensors, MESSR, VTIR and MSR. 2 HDDTs were brought back to Japan; they are composed of 13 paths acquired at the beginning of the system operation. Quick look films of these data were made, and some typical scenes of MESSR, VTIR and MSR were processed at NASDA EOC. Interesting features such as a giant iceberg are found among these processed images. Some limits of practical use of MESSR depending on the gain and solar elevation angle are discussed. departmental bulletin paper